Transposon expression in the Drosophila brain is driven by neighboring genes and diversifies the neural transcriptome - Treiber, CD; Waddell, S (Cold Spring Harbor Laboratory Press, 2020)
Somatic transposon expression in neural tissue is commonly considered as a measure of mobilization and has therefore been linked to neuropathology and organismal individuality. We combined genome sequencing data with single-cell mRNA sequencing of the same inbred fly strain to map transposon expression in the Drosophila midbrain and found that transposon expression patterns are highly stereotyped. Every detected transposon is resident in at least one cellular gene with a matching expression pattern. Bulk RNA sequencing from fly heads of the same strain revealed that coexpression is a physical link in the form of abundant chimeric transposon-gene mRNAs. We identified 264 genes where transposons introduce cryptic splice sites into the nascent transcript and thereby significantly expand the neural transcript repertoire. Some genes exclusively produce chimeric mRNAs with transposon sequence; on average, 11.6% of the mRNAs produced from a given gene are chimeric. Conversely, most transposon-containing transcripts are chimeric, which suggests that somatic expression of these transposons is largely driven by cellular genes. We propose that chimeric mRNAs produced by alternative splicing into polymorphic transposons, rather than transposon mobilization, may contribute to functional differences between individual cells and animals.